Disinfection of Viruses - Nims, Raymond W.; Khalid Ijaz, M. (IntechOpen, 2022)
Each of the chapters in Disinfection of Viruses touches on virucidal efficacy for SARS-CoV-2, the causative agent for the COVID-19 disease, or enveloped viral surrogates. SARS-CoV-2 is an enveloped virus of the Coronaviridae family and therefore is expected to be susceptible to all classes of microbicides. The book is divided into three sections. Section 1: "Microbicides for Viral Inactivation," includes chapters on the efficacy of chemical virucides, Section 2: "Physical Inactivation Approaches," includes a chapter on the efficacy of gamma irradiation, ultraviolet light, and heat for inactivating coronaviruses, and Section 3: "Viral Persistence and Disinfection," includes data on viral persistence for SARS-CoV-2, as these data inform the need for and the approaches that might be used for disinfection.